An investigation of relationship between corporate governance and financial performance of savings and credit cooperative Societies: A case of Tanga region - Olomy, Cletus C. (Mzumbe University, 2025)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of degree of Master of Business Administration (MBA-CM) of Mzumbe University